2020
DOI: 10.1016/j.jhealeco.2020.102302
|View full text |Cite
|
Sign up to set email alerts
|

Did parental involvement laws grow teeth? The effects of state restrictions on minors’ access to abortion

Abstract: Any opinions expressed in this paper are those of the author(s) and not those of IZA. Research published in this series may include views on policy, but IZA takes no institutional policy positions. The IZA research network is committed to the IZA Guiding Principles of Research Integrity. The IZA Institute of Labor Economics is an independent economic research institute that conducts research in labor economics and offers evidence-based policy advice on labor market issues. Supported by the Deutsche Post Founda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 23 publications
2
19
0
Order By: Relevance
“…Finally, family structure (e.g., cohabitation) and parental characteristics (e.g., age and education of mother) differ significantly by geography and time, and these differences may affect child-parent relationships and the composition of teens at risk of being affected by PI laws. 2 Overall, there are ample 1 The literature consists of state-specific studies (Cartoof and Klerman 1986;Colman et al 2008;Ellertson 1997;Henshaw 1995;Kaestner 1996, 2001;Joyce et al 2006;MacAfee et al 2015;Ralph et al 2018;Ramesh et al 2016;Rogers et al 1991) and analyses using a broader set of states (Haas-Wilson 1996;Levine 2003;Myers and Ladd 2017;New 2011;Ohsfeldt and Gohmann 1994). After reviewing this literature, we conclude that results from these studies indicate that PI laws decreased abortions among minors and that an effect size of 15% is typical, although there is meaningful variation across studies.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Finally, family structure (e.g., cohabitation) and parental characteristics (e.g., age and education of mother) differ significantly by geography and time, and these differences may affect child-parent relationships and the composition of teens at risk of being affected by PI laws. 2 Overall, there are ample 1 The literature consists of state-specific studies (Cartoof and Klerman 1986;Colman et al 2008;Ellertson 1997;Henshaw 1995;Kaestner 1996, 2001;Joyce et al 2006;MacAfee et al 2015;Ralph et al 2018;Ramesh et al 2016;Rogers et al 1991) and analyses using a broader set of states (Haas-Wilson 1996;Levine 2003;Myers and Ladd 2017;New 2011;Ohsfeldt and Gohmann 1994). After reviewing this literature, we conclude that results from these studies indicate that PI laws decreased abortions among minors and that an effect size of 15% is typical, although there is meaningful variation across studies.…”
Section: Introductionmentioning
confidence: 96%
“…Currently, 37 states enforce PI laws, and the widespread geographic coverage of current PI laws may make it more difficult for teens to avoid compliance by traveling to another state. For example, Myers and Ladd (2017) reported that the average distance to avoid a PI law increased from 55 miles in 1992 to 454 miles in 2017; thus, the effect of PI laws on abortion may have increased over time. Second, methods of contraception have changed over time, and the use of different methods varies by region.…”
Section: Introductionmentioning
confidence: 99%
“…Our paper, like Lindo and Pineda‐Torres (2019), adds to our understanding of how more recent mandatory waiting period legislation has changed the abortion landscape. Recent analyses of the effects of parental consent laws on abortions (Joyce, Kaestner, & Ward., 2019; Myers & Ladd, 2020) suggest that the effects of abortion legislation vary across both geographic contexts and time periods, highlighting the importance of revisiting the effects of laws such as these.…”
Section: Introductionmentioning
confidence: 99%
“…Here, het ero ge ne ity is Access to the EC Pill and Women's Reproductive Health in Chile deter mined by inten sity of pol icy adop tion. Such mod els documenting het ero ge ne ity in a dif fer enceindif fer ences set ting are fre quently esti mated; see, for exam ple, Bhalotra and Venkataramani (2015) (by race/age) and Myers and Ladd (2020) (by expo sure time). Finally, for com plete ness, we doc u ment effects based on a sin glecoef f cient, twoway fxedeffects model, in which the EC Pill indi ca tor from Eq.…”
Section: Methodsmentioning
confidence: 99%